2021
DOI: 10.1021/acs.jpcc.1c01209
|View full text |Cite
|
Sign up to set email alerts
|

Confinement-Driven “Flexible” Acidity Properties of Porous Zeolite Catalysts with Varied Probe-Assisted Solid-State NMR Spectroscopy

Abstract: Although the acidity properties and pore confinement effect inside porous zeolite catalysts have been extensively explored to correlate with their catalytic performances, a comprehensive understanding regarding the influence of confinement effect on the acidity properties is still lacking. Herein, with the employment of two commonly used nuclear magnetic resonance (NMR) probe molecules, namely pyridine-d 5 and trimethylphosphine oxide (TMPO) with different shapes and size dimensions, the influence of the confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…From the perspective of acidic strength, the bridged Si-OH-Al Brønsted acidic sites (BAS) in zeolites is usually considered as a moderate acid based on their ensembleaveraged deprotonation energies, 6 but the confinement effect of the zeolite framework can compensate this deficiency and present a higher apparent acidity with bulky probe molecules. [7][8][9][10][11] More importantly, the carbocation chemistry in the cages or channels of zeolites not only depends on the stability of the carbocations but also the systemic influence of carbocation-like species (including transition states and intermediates) on the potential energy profiles. Two types of carbocations are frequently reported in zeolite-catalyzed reactions, i.e., chain carbenium ions and cyclic carbenium ions.…”
Section: Xianfeng Yimentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of acidic strength, the bridged Si-OH-Al Brønsted acidic sites (BAS) in zeolites is usually considered as a moderate acid based on their ensembleaveraged deprotonation energies, 6 but the confinement effect of the zeolite framework can compensate this deficiency and present a higher apparent acidity with bulky probe molecules. [7][8][9][10][11] More importantly, the carbocation chemistry in the cages or channels of zeolites not only depends on the stability of the carbocations but also the systemic influence of carbocation-like species (including transition states and intermediates) on the potential energy profiles. Two types of carbocations are frequently reported in zeolite-catalyzed reactions, i.e., chain carbenium ions and cyclic carbenium ions.…”
Section: Xianfeng Yimentioning
confidence: 99%
“…Also, this is the reason why the confinement effect influences the measurement of acidity based on the interaction of probe molecules with BAS. 9 Moreover, zeolites with small channels (such as mordenite) can be characterized to be a superacid by large probe molecules (such as Hammett indicators), 7,11 where these abnormal results appear because the Hammett indicator under the strong confinement effect also changes colour without protonation. 10 Therefore, the super-acidity of zeolites from the perspective of apparent acidity related to the size of guest species and the better compatibility between the zeolite framework and carbocations lead to the higher stability of carbocations in zeolites.…”
Section: Molecular Understanding Of Confined Carbocations In Zeolitesmentioning
confidence: 99%
“…The secondsphere around the FLPs could tune their apparent acid and base strength via van der Waals and electrostatic interactions, as was recently suggested for Brønsted acid sites in zeolites. 149 There are also a lot of design parameters in zeolites: topology, density of aluminum sites, location of aluminum sites, location of dealumination defects, and the types of metals doped into the material. The zeolite can be tuned to have specific Lewis acid− base pairs as well as particular distances between them.…”
Section: Frustrated Lewis Pairsmentioning
confidence: 99%
“…The Dyballa group described a method for the quantification of Brønsted acid sites located on surfaces and in pores of hierarchical zeolite catalysts using the probe triphenylphosphine by multinuclear MAS NMR . Zheng and coworkers reported that pore confinement significantly affects the electronic structure of adsorbed species by van der Waals and electrostatic interactions using varied probe-assisted solid-state NMR . The nature and spectroscopic expression of external surface sites of zeolites such as silanol–Al sites by the combination of MAS NMR and Fourier-transform infrared spectroscopy (FT-IR) with DFT calculations was investigated by the Chizallet group .…”
mentioning
confidence: 99%
“…22 Zheng and coworkers reported that pore confinement significantly affects the electronic structure of adsorbed species by van der Waals and electrostatic interactions using varied probe-assisted solidstate NMR. 23 The nature and spectroscopic expression of external surface sites of zeolites such as silanol−Al sites by the combination of MAS NMR and Fourier-transform infrared spectroscopy (FT-IR) with DFT calculations was investigated by the Chizallet group. 24 Koller and coworkers observed additional 1 H− 27 Al dipolar interactions in an extra-large pore zeolite with high aluminum ordering using 1 H{ 27 Al} rotational echo adiabatic passage double-resonance.…”
mentioning
confidence: 99%